2005
DOI: 10.1080/01676830490916064
|View full text |Cite
|
Sign up to set email alerts
|

A Rapidly Fatal Case of T-Cell Lymphoma Presenting as Idiopathic Orbital Inflammation

Abstract: A 41-year-old Caucasian woman presented with a painful, red right eye with minimal systemic symptomatology, and was initially diagnosed with right idiopathic orbital inflammation. Ten days later, she developed abdominal and respiratory symptoms; this led to her demise within a further week. Post-mortem examination demonstrated widespread extranodal NK/T- cell lymphoma (nasal type), involving the right posterior orbit, lungs, uterus, left adrenal gland, pericardium and meninges. Thorough physical examination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Termote et al 19 reported a case series comprising three patients with periorbital involvement from NKTL who all developed painless eyelid swelling, which, along with a history of chronic sinusitis with nasal congestion, masqueraded as periorbital cellulitis. The diagnosis was established from biopsies of the orbital mass, and in one case of the cervical lymphadenopathy 17 . Similarly, 50% and 16.7% of the patients in group 1 presented with symptoms mimicking orbital cellulitis and pseudotumor, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Termote et al 19 reported a case series comprising three patients with periorbital involvement from NKTL who all developed painless eyelid swelling, which, along with a history of chronic sinusitis with nasal congestion, masqueraded as periorbital cellulitis. The diagnosis was established from biopsies of the orbital mass, and in one case of the cervical lymphadenopathy 17 . Similarly, 50% and 16.7% of the patients in group 1 presented with symptoms mimicking orbital cellulitis and pseudotumor, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these composite diagnostic processes confirming the BIOMED-2 PCR assay results can be limitedly useful in diagnosing equivocal lymphomas that are caused by previous use of corticosteroids 13 . This diagnostic attempt is of clinical value because it may reduce the risk of under treatment of undiagnosed OAL 25 …”
Section: Discussionmentioning
confidence: 99%
“…There is a report of a 41year-old woman, although Caucasian, who was initially diagnosed with idiopathic orbital inflammation and later died of widespread ENKTL. 9 Another report demonstrated that NKTL comprises less than 1% of OAL in Western countries. 5 However, NKTL is often a fatal disease, especially when the diagnosis is delayed, as in our case, and has been shown to be more prevalent in East Asia than in Western countries.…”
Section: To the Editormentioning
confidence: 99%